Polyethylene resin for melt spinning and preparation and application thereof
By using a method of purifying diluent and hot channel tensile orientation in polymerization, the high crystal point and wire breaking rate caused by polyethylene resin impurities in melt spinning is solved, and the stable production of high-performance fibers and process simplification is achieved. , reducing costs and footprint.
Patent Information
- Application Number
- CN202411508280.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-03
AI Technical Summary
In the existing melt spinning technology, impurities in polyethylene resin lead to crystal point problems and high filament breakage rate, affecting the efficiency and quality of fiber preparation, and the process is complicated, so it has not been industrialized in China.
By performing polymerization in the reactor, washing with purified diluent and solid-liquid separation, a polyethylene resin with narrow molecular weight distribution is obtained, and the tensile orientation is performed directly in the hot channel, simplifying the spinning process and reducing the crystal point and Wire breaking rate.
It greatly reduces the crystal point and wire breakage rate during spinning, simplifies the process flow, reduces production costs and floor area, and improves the quality and production efficiency of high-performance fibers.
Smart Images

Figure CN119241748A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer material preparation, and relates to a polyethylene resin for melt spinning and its preparation and application. Background Art
[0002] In recent years, the use of high-performance fibers has gradually increased in the civilian field. They can be applied to high-end fiber products and are widely used in the fields of medicine, fishery, and protective equipment. The commonly used ultra-high molecular weight polyethylene fiber is relatively reluctant to be used in the civilian field due to high cost, diluent residue, and complex process flow. However, low-cost, medium-strength fiber products without diluent residue are gradually favored by the civilian high-performance fiber field. Such medium-strength fiber products are mainly obtained using the melt spinning process.
[0003] At present, Chinese patents CN1646739A, CN109521054B, CN111494976B, CN115339088A, CN115029810A, etc. have disclosed methods for preparing high-performance fibers using polyethylene resins with narrow molecular weight distribution. However, these methods all require multi-stage stretching after the spinning plate is sprayed out, rolled up, cooled, and then heated up. The fiber preparation process is relatively long, and there is a crystal point problem during subsequent melt spinning. This type of spinning method will only affect the spinning performance during the spinning process of coarse denier fibers, and will even directly cause broken fibers during the spinning process of fine denier fibers. This is also the main reason why the fiber preparation methods described in this type of patents have not yet been industrialized in China.
[0004] Therefore, in order to solve the above problems, it is necessary to develop a high-performance polyethylene fiber melt spinning resin suitable for industrial production, with low impurity content in raw materials and which can further simplify the spinning process. Summary of the invention
[0005] The purpose of the present invention is to provide a polyethylene resin for melt spinning and its preparation and application, so that the crystal point and the broken wire rate in the spinning process are greatly reduced, and a stable high-performance fiber melt spinning production process can be formed.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] In one aspect, the present invention provides a method for preparing a polyethylene resin for melt spinning, comprising the following steps:
[0008] (1) adding raw materials including a main catalyst, a co-catalyst, a diluent, and ethylene into a reactor to carry out a polymerization reaction to obtain a slurry blend containing a resin and a diluent;
[0009] (2) washing the slurry blend with a purified diluent during the discharge process, and then separating the solid from the liquid;
[0010] (3) After solid-liquid separation, the resin is dried to obtain a polyethylene resin product.
[0011] Furthermore, the main catalyst is a single active site catalyst, a Ziegler-Natta system catalyst, or a composite of several thereof;
[0012] The co-catalyst is one or a combination of triethylaluminum, triisobutylaluminum, and diethylaluminum chloride;
[0013] The diluent is a saturated hydrocarbon with a boiling point of -20°C to 70°C.
[0014] Here, in the present invention, by further optimizing the catalyst and other components, a polyethylene resin with a narrower molecular weight distribution can be polymerized, thereby providing a certain melt strength and spinnability in the post-spinning process, while obtaining higher strength fiber product mechanical properties, so that the product meets the requirements for use in the field of higher performance fibers.
[0015] Furthermore, the diluent is one or a mixture of n-hexane, isobutane, isopentane and cyclohexane.
[0016] Furthermore, the polymerization temperature is 50°C-90°C and the pressure is 0.8-4MPa.
[0017] Furthermore, in step (2), the purification process of the diluent includes de-weighting and distillation, so that the diluent purity reaches above 99.8%. Here, the specific process and related parameters of de-weighting and distillation are conventional techniques in the art.
[0018] Furthermore, in step (2), the amount of the purified diluent used is greater than 10 wt % of the slurry blend output.
[0019] Furthermore, the solid-liquid separation method is filter pressing or centrifugation.
[0020] Furthermore, the drying treatment method is any one of hot nitrogen drying, low boiling point oil extraction followed by drying, and fresh diluent washing followed by drying. Specifically, the drying temperature can be 60-130°C.
[0021] Furthermore, the diluent obtained after solid-liquid separation is purified and then circulated to step (2) to wash the output material.
[0022] Furthermore, the reactor can be a loop reactor or a tank reactor.
[0023] In another aspect, the present invention provides a polyethylene resin for melt spinning, which is prepared by any of the above preparation methods. Specifically, the obtained polyethylene resin product (7) meets the molecular structure requirements of a weight average molecular weight of 150,000-900,000 and a molecular weight distribution of less than 4.0.
[0024] In a third aspect, the present invention provides a use of a polyethylene resin for melt spinning in the preparation of high-performance polyethylene fiber products.
[0025] In a fourth aspect, the present invention provides a method for preparing high-performance polyethylene fibers based on melt spinning, comprising the following steps:
[0026] (1) adding raw materials including a main catalyst, a co-catalyst, a diluent, and ethylene into a reactor to carry out a polymerization reaction to obtain a slurry blend containing a resin and a diluent;
[0027] (2) washing the slurry blend with a purified diluent during the discharge process, and then separating the solid from the liquid;
[0028] (3) drying the resin after solid-liquid separation to obtain a polyethylene resin product;
[0029] (4) The obtained polyethylene resin product is used as a polyethylene raw material, compounded with processing aids including antioxidants and lubricants, and then fed into a screw extruder for melt extrusion, and fibers are ejected through a spinneret, and directly stretched and oriented in a hot tunnel connected to the spinneret outlet to obtain a fiber product.
[0030] Furthermore, the raw materials used in the process of preparing the polyethylene resin product can be optimized in the aforementioned method.
[0031] Further, the processing aids here can be the commonly used additives for preparing polyethylene fibers. For example, the antioxidant can be 2,6-di-tert-butyl-p-cresol, 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl ester, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, etc., and the lubricant can be zinc stearate, calcium stearate, etc. At the same time, in addition to antioxidants and lubricants, other processing aids can also be introduced as needed.
[0032] Furthermore, the temperature of the spinneret is 220-260°C.
[0033] Further, the hot tunnel is preferably divided into two interval sections, and the two sections can be continuous temperature sections or 1-5m apart. More preferably, two or more interval sections are used. When there are two interval sections, the temperature of the first section is higher than the temperature of the second section, and the temperature of the second section can be divided into variable multi-stage temperatures. Exemplarily, the temperature of the first section can be 150-170°C, and the temperature of the second section can be a three-stage temperature of 90-160°C. At the same time, the fiber stays in the first section for 0.5-120 seconds, and the fiber stays in the second section for 0.5-180 seconds.
[0034] Furthermore, after direct orientation stretching in the hot tunnel, the film can be further stretched in multiple stages by hot rollers.
[0035] The present invention has found through research that a key problem in existing melt spinning is the crystal point problem caused by impurities in the resin raw material. Therefore, the present invention uses a slurry reactor to polymerize polyethylene, adds a purified diluent to the discharge line for washing, and then separates the diluent through a subsequent solid-liquid separation process before high-temperature drying. The present invention has found through research that the melt spinning special resin obtained by polymerization through this method greatly reduces the trace impurities generated in the ethylene polymerization reaction in the spinning resin, and the polyethylene resin obtained by the method has a greatly reduced crystal point content in the fiber obtained by spinning, and the filament breakage rate is greatly reduced.
[0036] In addition, the present invention surprisingly found that the polyethylene resin obtained by polymerization based on the above process has a greatly improved fiber melt strength after exiting the spinneret during the melt spinning process. After the polyethylene melt is extruded from the spinneret, it can directly pass through a hot tunnel at high temperature, where it can be oriented and stretched, and then directly rolled up to obtain a melt-spun high-performance fiber product after oriented and stretched. There is no need to first cool and solidify the melt after exiting the spinneret, and then heat it up for multi-stage stretching to obtain a fiber product, and the overall process is greatly simplified.
[0037] At the same time, for the spinning process of the polyethylene resin prepared by the present invention, if the length of the hot tunnel is insufficient, the problem of insufficient stretching ratio can be further compensated by hot roller stretching. With the advantage of improved resin melt strength, the floor space occupied by the entire melt spinning process can be greatly reduced, the process can be simplified, and the preparation cost of high-performance fiber melt spinning can be further reduced.
[0038] In the solid-liquid separation unit of the present invention, the diluent with a low boiling point can be separated by low temperature and high pressure to prevent vaporization from occurring during the separation process.
[0039] In the present invention, the amount of washing diluent used in the discharge line is more than 10% of the mass ratio of the discharge amount. As the amount of washing diluent added increases, the spinnability of the obtained resin increases accordingly.
[0040] The resin synthesized by the present invention has the following advantages over the existing melt spinning resin:
[0041] 1) The crystal point and broken fiber rate in the spinning process are greatly reduced, which can form a stable high-performance fiber melt spinning production process.
[0042] 2) The improvement of resin enables a simpler new melt spinning process to be realized, which greatly reduces the production cost of high-performance fiber melt spinning and the area occupied by melt spinning.
[0043] 3) Improvements in resin preparation technology have greatly improved the quality of high-performance fibers produced through spinning. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 is a picture of the fiber product prepared in Comparative Example 3;
[0045] Figure 2 is a picture of the fiber product prepared in Comparative Example 2;
[0046] Figure 3 This is a picture of the fiber of Example 1 entering the hot tunnel from the spinneret. DETAILED DESCRIPTION
[0047] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0048] In the following embodiments, the polyethylene resin can be obtained by ethylene polymerization using a single active center polyethylene catalyst, including supported and unsupported metallocene system catalysts or non-metallocene system catalysts. The catalysts described in patents CN109306029A and CN116535548A can be used. Specifically, the preparation process of the polyethylene raw material in this embodiment is as follows:
[0049] (1) Add n(methanol):n(original carrier Mg(OH)2)=5:1 into the reaction bottle, heat to 100°C, add diisobutyl phthalate, stir at high speed, stirring speed 500 rpm, react for 4 hours, after the reaction is completed, quickly press the resulting mixture into a large amount of -15°C n-hexane to fix the solid. The resulting solid is placed in a nitrogen atmosphere and heated to 60°C, maintained for 5 hours to obtain the desired carrier Mg1, with an average particle size of 150 μm and a specific surface area of 450 m / g. Dissolve the metal catalyst in toluene, add triethylaluminum, stir evenly to obtain a catalyst solution; add the carrier Mg1, stir evenly, and obtain the supported catalyst C1.
[0050] (2) Weigh 0.5 g of ammonium bifluoride and dissolve it in 20 mL of water. The resulting colorless clear liquid is added dropwise to 10 g of silica gel (Sylopol 955) and placed in an oven at 100° C. to dry. After the water evaporates, the mixture is calcined at 600° C. in a nitrogen atmosphere for 3 hours. After cooling, 0.2 g of triethylaluminum is added and the reaction is continued to obtain an active silica gel carrier S1.
[0051] Under argon protection, 5.0 g of active silica gel carrier S1 was suspended in 5 mL of toluene in a 100 mL reaction bottle, 10.0 mg of phenoxyimine zirconium complex Zr5 and 10.0 mg of bis(cyclopentadienyl) zirconium dichloride were weighed and dissolved in 5.0 mL of toluene, and the mixed solution was added to the toluene suspension of active silica gel carrier S1, stirred at room temperature for 1 hour, filtered, washed with toluene twice, and vacuum dried to obtain catalyst powder C2.
[0052] The antioxidant used is obtained by mixing antioxidant 1010 and antioxidant PS802 in a mass ratio of 2:8.
[0053] Test method for fiber tensile properties: The tensile properties of fibers were tested using the method of GB / T19975-2005.
[0054] The rest of the raw materials or processing techniques, unless otherwise specified, are conventional commercially available raw materials or processing techniques in the art.
[0055] Example 1
[0056] Add polyethylene catalyst, triethylaluminum and n-hexane into 7m 3 In the kettle reactor, 30 g of catalyst C1, 540 g of triethylaluminum and 3.6 tons of n-hexane were added. After the reactor was started and stirred, the kettle was heated to 80 ° C, ethylene gas was introduced, and the reactor pressure was maintained at 1 MPa. After 3 hours of reaction, ethylene was stopped from entering. After the pressure was reduced, the slurry reactants were transported to the filter press, and the purified n-hexane solvent was supplemented in front of the filter press at 10 tons / hour. The purified n-hexane solvent and the slurry reactants were separated from the solid by the filter press. The separated polyethylene wet material was dried by purging with nitrogen at 90 ° C to obtain polyethylene dry material. The weight average molecular weight of the obtained dry material was 150,000, and the molecular weight distribution was 2.5.
[0057] The polyethylene dry material is compounded with antioxidant, zinc stearate and calcium stearate in a ratio of 99:0.4:0.3:0.3 (mass) and then added to the screw extruder for extrusion. The screw extruder barrel is divided into five sections in turn, and the temperature of each section is 100℃, 190℃, 190℃, 190℃, and 190℃. The fiber is sprayed out through the spinneret, and the spinneret temperature is 240℃. The spinneret outlet is connected to the hot tunnel, which is divided into two sections in the front and back directions. The two sections are continuous. The temperature of the first section is 160℃ and its length is 8m. The temperature of the second section is divided into three levels, namely 160℃, 140℃, and 120℃, and the lengths are 3m, 4m, and 4m, respectively. After passing through the spinneret and the hot tunnel, the fiber is directly wound at a speed of 500m / min, and the final fiber product can be obtained without cooling and multi-stage stretching processes. The fiber tensile strength reaches 15cN / dtex.
[0058] Example 2
[0059] Fill the loop reactor with isobutane and heat it to 70°C. The reactor pressure is 4.1MPa. Turn on the axial flow pump and add ethylene, catalyst C1, triisobutylaluminum and isobutane at the same time. The amount of ethylene added is 3 tons / hour, the amount of isobutane added is 5.5 tons / hour, the amount of catalyst added is 0.4kg / hour, and the amount of triisobutylaluminum added is 0.4kg / hour. The discharge of the loop slurry is about 8.5 tons / hour. The purified isobutane is injected at the discharge port at 10 tons / hour, and the slurry is separated into solid and liquid by filter pressing. The separated wet material enters the flash tank for flash evaporation and then enters the degassing bin. After purging with 60°C nitrogen in the degassing bin, the material is discharged. The weight average molecular weight of the dry material is 250,000, and the molecular weight distribution is 2.5.
[0060] Polyethylene dry material is compounded with antioxidant, zinc stearate and calcium stearate in a ratio of 99:0.4:0.3:0.3 and then added to a screw extruder for extrusion. The screw extruder barrel is divided into five sections in sequence, and the temperature of each section is 100℃, 190℃, 190℃, 190℃, and 190℃. The fiber is sprayed out through the spinneret, and the spinneret temperature is 240℃. The spinneret outlet is connected to the hot tunnel, which is divided into two sections in the front and back direction, with a spacing of 1m. The temperature of the first section is 160℃ and its length is 6m, and the temperature of the second section is 130℃ and its length is 8m. After passing through the spinneret and the hot tunnel, the fiber is directly wound at a speed of 300m / min, and the final fiber product can be obtained without cooling and multi-stage stretching processes. The fiber tensile strength reaches 18cN / dtex.
[0061] Example 3
[0062] Fill the loop reactor with n-hexane and heat it to 60°C. The reactor pressure is 2MPa. Turn on the axial flow pump and add ethylene, catalyst C2, and diethylaluminum chloride at the same time. The amount of ethylene added is 3 tons / hour, the amount of n-hexane added is 5.5 tons / hour, the amount of catalyst added is 0.4kg / hour, and the amount of diethylaluminum chloride added is 0.4kg / hour. The output of the loop slurry is about 8.5 tons / hour. The purified n-hexane is injected at the discharge port at 8 tons / hour, and the slurry is separated into solid and liquid by centrifugal separation. The separated wet material enters the screw belt dryer, and 120°C water vapor is introduced into the screw belt and the interlayer of the wall of the dryer, and 90°C nitrogen is introduced into the dryer. The dryer is discharged and the dry material is obtained by air conveying. The weight average molecular weight of the dry material is 900,000, and the molecular weight distribution is 3.2.
[0063] Polyethylene dry material is compounded with antioxidant, zinc stearate, calcium stearate and polyethylene wax in a ratio of 98:0.4:0.3:0.3:1 and then added to the screw extruder for extrusion. The temperature of the screw extruder barrel is divided into five sections, each of which is 100℃, 200℃, 200℃, 200℃ and 200℃. The fiber is sprayed out through the spinneret, and the spinneret temperature is 240℃. The spinneret outlet is connected to the hot tunnel, which is divided into two sections in the front and back directions. The two sections are continuous. The temperature of the first section is 190℃ and its length is 10m. The temperature of the second section is divided into three levels, namely 140℃, 150℃ and 130℃, and the lengths are 5m, 7m and 6m respectively. After passing through the spinneret and the hot tunnel, the fiber is stretched by a hot roller. After being stretched 2.5 times at a hot roller temperature of 130℃, it is wound at a speed of 200m / min. The final fiber product can be obtained without cooling and hot box multi-stage stretching process. The fiber tensile strength reaches 23cN / dtex.
[0064] Example 4
[0065] Add polyethylene catalyst, triethylaluminum, n-hexane and other raw materials into 7m 3 In the kettle reactor, the amount of catalyst C2 is 30g, the amount of triisobutyl aluminum is 240g, the amount of triethyl aluminum added is 300g, and the amount of n-hexane added is 3.6 tons. After the reactor is started and stirred, the kettle is heated to 80°C, ethylene gas is introduced, and the reactor pressure is maintained at 4MPa. After 3 hours of reaction, the ethylene is stopped from entering, and the slurry reactant is transported to the filter press. The purified isobutane solvent is supplemented in front of the filter press at a rate of 10 tons / hour. The purified isobutane solvent and the slurry reactant are extracted and separated from the solid and liquid by the filter press. The separated polyethylene wet material enters the flash tank for flash evaporation, and then purged and dried by 90°C nitrogen to obtain polyethylene dry material. The weight average molecular weight of the obtained dry material is 400,000, and the molecular weight distribution is 3.9.
[0066] Polyethylene dry material is compounded with antioxidant, zinc stearate, calcium stearate and white oil in a ratio of 98.5:0.4:0.3:0.3:0.5 and then added to the screw extruder for extrusion. The temperature of the screw extruder barrel is divided into five sections, each of which is 100°C, 190°C, 190°C, 190°C and 190°C. The fiber is sprayed out through the spinneret, and the spinneret temperature is 240°C. The spinneret outlet is connected to the hot tunnel, which is divided into two sections in the front and back direction, with a spacing of 2m between the two sections. The temperature of the first section is 160°C and its length is 8m. The temperature of the second section is divided into two levels (two continuous levels), which are 140°C and 120°C respectively, and the lengths are 4m and 4m respectively. After passing through the spinneret and hot tunnel, the fiber is drawn by hot rollers, stretched 1.5 times at a hot roller temperature of 130°C, and then wound at a speed of 300m / min. The final fiber product can be obtained without cooling and multi-stage stretching processes. The fiber tensile strength reaches 18cN / dtex.
[0067] Example 5
[0068] Fill the loop reactor with n-hexane and heat it to 60°C. The reactor pressure is 4MPa. Turn on the axial flow pump and add ethylene, catalyst C2, and diethylaluminum chloride at the same time. The amount of ethylene added is 3 tons / hour, the amount of n-hexane added is 5.5 tons / hour, the amount of catalyst added is 0.4kg / hour, and the amount of diethylaluminum chloride added is 0.4kg / hour. The discharge of the loop slurry is about 8.5 tons / hour. Purified isobutane is injected at the discharge port at 20 tons / hour, and the slurry is separated into solid and liquid by centrifugal separation. The separated wet material enters the flash tank for flash evaporation and then enters the degassing bin. After purging with 60°C nitrogen in the degassing bin, the dry material is obtained by air conveying. The weight average molecular weight of the dry material is 900,000, and the molecular weight distribution is 3.2.
[0069] Polyethylene dry material is compounded with antioxidant, zinc stearate, calcium stearate and polyethylene wax in a ratio of 98:0.4:0.3:0.3:1 and then added to the screw extruder for extrusion. The temperature of the screw extruder barrel is divided into five sections, each of which is 100℃, 200℃, 200℃, 200℃ and 200℃. The fiber is sprayed out through the spinneret, and the spinneret temperature is 240℃. The spinneret outlet is connected to the hot tunnel, which is divided into two sections in the front and back directions. The two sections are continuous. The temperature of the first section is 160℃ and its length is 5m. The temperature of the second section is divided into three levels, namely 140℃, 130℃ and 90℃, and the lengths are 3m, 4m and 5m respectively. After passing through the spinneret and the hot tunnel, the fiber is stretched by a hot roller. After being stretched 2.5 times at a hot roller temperature of 130℃, it is wound at a speed of 200m / min. The final fiber product can be obtained without cooling and hot box multi-stage stretching process. The fiber tensile strength reaches 25cN / dtex.
[0070] Comparative Example 1
[0071] The same polyethylene resin raw material polymerization method as in Example 1 was adopted, and the purified n-hexane was not supplemented at the discharge end. Other parameters and operations were the same.
[0072] Polyethylene dry material is compounded with antioxidant, zinc stearate and calcium stearate in a ratio of 99:0.4:0.3:0.3 and then added to the screw extruder for extrusion. The temperature of the screw extruder barrel is divided into five sections, each of which is 100℃, 190℃, 190℃, 190℃ and 190℃. The fiber is sprayed out through the spinneret, and the spinneret temperature is 240℃. The spinneret outlet is connected to the hot tunnel, which is divided into two sections in the front and back direction. The two sections are continuous. The temperature of the first section is 160℃ and its length is 8m. The temperature of the second section is divided into three levels, namely 160℃, 140℃ and 120℃, and the lengths are 3m, 4m and 4m respectively. The fiber is broken after passing through the spinneret and the hot tunnel, and cannot be directly reeled.
[0073] After the fiber passes through the spinneret, it is directly wound at a speed of 200 m / min without passing through the hot tunnel. The wound fiber is then unwound at a speed of 10 m / min, passed through the first hot box (temperature of 120°C, length of 15 m), and wound at a speed of 30 m / min. The wound fiber is unwound at a speed of 20 m / min, passed through the second hot box (temperature of 130°C, length of 18 m), and wound at a speed of 46 m / min to obtain multi-stage stretched fibers with a stretching ratio of 7 times. The obtained fibers have a tensile strength of 15 cN / dtex.
[0074] Comparative Example 2
[0075] The same polyethylene resin raw material polymerization method as in Example 2 was adopted, and the slurry reactants and supplementary purified isobutane were directly flashed and degassed without solid-liquid separation to obtain a dried raw material.
[0076] The polyethylene dry material is compounded with antioxidant, zinc stearate and calcium stearate in a ratio of 99:0.4:0.3:0.3 and then added to the screw extruder for extrusion. The screw extruder barrel temperature is divided into five sections, each section temperature is 100℃, 190℃, 190℃, 190℃, 190℃. The fiber is sprayed out through the spinneret, and the spinneret temperature is 240℃. The spinneret outlet is connected to the hot tunnel, which is divided into two sections in the front and back direction, with a spacing of 1m between the two sections. The temperature of the first section is 160℃ and its length is 6m, and the temperature of the second section is 130℃ and its length is 8m. The fiber is broken after passing through the spinneret and the hot tunnel, and cannot be directly reeled.
[0077] After the fiber passes through the spinneret, it is directly wound at a speed of 200m / min without passing through the hot tunnel. The wound fiber is then unwound at a speed of 10m / min and passed through the first hot box (hot box temperature 120℃, length 12m) and wound at a speed of 30m / min. The wound fiber is unwound at a speed of 20m / min and passed through the second hot box (hot box temperature 125℃, length 18m) and wound at a speed of 46m / min to obtain multi-stage stretched fibers with a stretching ratio of 7 times. The fibers have a small amount of crystal points and a small amount of broken fibers.
[0078] Comparative Example 3
[0079] The same polyethylene resin raw material polymerization method as in Example 1 was used, and no weight removal treatment was performed at the rear end of n-hexane separation (i.e., it was directly circulated for washing without purification treatment), and other parameters and operations were the same.
[0080] Polyethylene dry material is compounded with antioxidant, zinc stearate and calcium stearate in a ratio of 99:0.4:0.3:0.3 and then added to the screw extruder for extrusion. The temperature of the screw extruder barrel is divided into five sections, each of which is 100℃, 190℃, 190℃, 190℃ and 190℃. The fiber is sprayed out through the spinneret, and the spinneret temperature is 240℃. The spinneret outlet is connected to the hot tunnel, which is divided into two sections in the front and back direction. The two sections are continuous. The temperature of the first section is 160℃ and its length is 8m. The temperature of the second section is divided into three levels, namely 160℃, 140℃ and 120℃, and the lengths are 3m, 4m and 4m respectively. The fiber is broken after passing through the spinneret and the hot tunnel, and cannot be directly reeled.
[0081] In addition, after the fiber passes through the spinneret, it is directly wound at a speed of 200m / min without passing through the hot tunnel. The wound fiber is then unwound at a speed of 10m / min and passed through the first hot box. The hot box temperature is 120℃, the length is 15m, and the winding speed is 20m / min. The wound fiber is unwound at a speed of 20m / min and passed through the second hot box. The hot box is 125℃, 18m, and wound at a speed of 50m / min to obtain multi-stage stretched fibers with a stretching ratio of 5 times. The fibers have many crystal points and a large number of broken fibers.
[0082] Comparative Example 4
[0083] The same polyethylene resin raw material polymerization method as in Example 1 was used, the polymerization temperature was 90° C., and other parameters and operations were the same. The obtained resin had a weight average molecular weight of 100,000 and a molecular weight distribution of 2.8.
[0084] The polyethylene dry material is compounded with antioxidant, zinc stearate and calcium stearate in a ratio of 99:0.4:0.3:0.3 and then added to the screw extruder for extrusion. The temperature of the screw extruder barrel is divided into five sections, each of which is 100℃, 190℃, 190℃, 190℃ and 190℃. The fiber is sprayed out through the spinneret, and the spinneret temperature is 240℃. The spinneret outlet is connected to the hot tunnel, which is divided into two sections in the front and back directions. The two sections are continuous. The temperature of the first section is 160℃ and its length is 8m. The temperature of the second section is divided into three levels, namely 160℃, 140℃ and 120℃, and the lengths are 3m, 4m and 4m respectively. The fiber is directly wound after passing through the spinneret and the hot tunnel, and the final fiber product can be obtained without cooling and multi-stage stretching processes. The fiber tensile strength is only 11cN / dtex.
[0085] Comparative Example 5
[0086] In a gas phase fluidized bed reactor, ethylene polymerization was carried out, and raw materials such as ethylene, catalyst C1, triisobutylaluminum, and isobutane were added. The amount of ethylene added was 3 tons / hour, the amount of catalyst added was 0.4 kg / hour, and the amount of triisobutylaluminum added was 0.4 kg / hour. The weight average molecular weight of the dry material obtained after discharge and degassing of the gas phase reactor was 230,000, and the molecular weight distribution was 2.7.
[0087] Polyethylene dry material is compounded with antioxidant, zinc stearate and calcium stearate in a ratio of 99:0.4:0.3:0.3 and then added to the screw extruder for extrusion. The temperature of the screw extruder barrel is divided into five sections, each of which is 100℃, 190℃, 190℃, 190℃ and 190℃. The fiber is sprayed out through the spinneret, and the spinneret temperature is 240℃. The spinneret outlet is connected to the hot tunnel, which is divided into two sections in the front and back direction. The two sections are continuous. The temperature of the first section is 160℃ and its length is 8m. The temperature of the second section is divided into three levels, namely 160℃, 140℃ and 120℃, and the lengths are 3m, 4m and 4m respectively. The fiber is broken after passing through the spinneret and the hot tunnel, and cannot be directly reeled.
[0088] After the fiber passes through the spinneret, it is directly wound at a speed of 200m / min without passing through the hot tunnel. The wound fiber is then unwound at a speed of 10m / min, passed through the first hot box (hot box temperature 120℃, length 12m) and wound at a speed of 30m / min, and the wound fiber is unwound at a speed of 20m / min, passed through the second hot box (hot box temperature 130℃, length 18m) and wound at a speed of 46m / min to obtain multi-stage stretched fibers with a stretching ratio of 7 times. The fibers have a small amount of crystal points and a small amount of broken fibers.
[0089] Table 1 Performance data of various embodiments and comparative examples
[0090]
[0091]
[0092]
[0093] Note: Figure 2 The middle circle part is the area with obvious crystal points.
[0094] From the above table and Figure 1 , Figure 2 It can be seen that the resin obtained by the specific polymerization method of the present invention can greatly simplify the spinning process during the melt spinning process, and the production mode of one extrusion line plus more than ten spinning lines can be changed to a mode where one extrusion line can complete the production, which reduces the cost and eliminates the problems of crystal points and broken wires during the spinning process, solving the industrialization problem of high-performance fiber melt spinning. However, the resin obtained by polymerization using a traditional gas phase reactor or not using the polymerization method used in the present invention has problems such as crystal points and broken wires, which affects the fiber quality and cannot be further industrialized for fiber products.
[0095] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a polyethylene resin for melt spinning, characterized in that: The following steps are involved: (1) adding raw materials including a main catalyst, a co-catalyst, a diluent, and ethylene into a reactor to carry out a polymerization reaction to obtain a slurry blend containing a resin and a diluent; (2) washing the slurry blend with a purified diluent during the discharge process, and then separating the solid from the liquid; (3) After solid-liquid separation, the resin is dried to obtain a polyethylene resin product.
2. The method for preparing a polyethylene resin for melt spinning according to claim 1, characterized in that: The main catalyst is a single active site catalyst, a Ziegler-Natta system catalyst, or a composite of several thereof; The co-catalyst is one or a combination of triethylaluminum, triisobutylaluminum, and diethylaluminum chloride; The diluent is a saturated hydrocarbon with a boiling point of -20°C to 70°C.
3. The method for preparing a polyethylene resin for melt spinning according to claim 1, characterized in that: The diluent is one of n-hexane, isobutane, isopentane and cyclohexane or a mixture of several of them.
4. The method for preparing a polyethylene resin for melt spinning according to claim 1, characterized in that: In step (2), the purification process of the diluent includes weight removal and distillation, so that the purity of the diluent reaches more than 99.8%.
5. The method for preparing a polyethylene resin for melt spinning according to claim 1, characterized in that: In step (2), the amount of the purified diluent used is at least 10 wt % of the slurry blend output.
6. The method for preparing a polyethylene resin for melt spinning according to claim 1, characterized in that: The solid-liquid separation method is filter pressing or centrifugation; The drying treatment method is any one of hot nitrogen drying, low boiling point oil extraction and drying, and fresh diluent washing and drying.
7. The method for preparing a polyethylene resin for melt spinning according to claim 1, characterized in that: The diluent obtained after solid-liquid separation is purified and then circulated to step (2) to wash the output material.
8. A polyethylene resin for melt spinning, prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the polyethylene resin for melt spinning as claimed in claim 8 in the preparation of high-performance polyethylene fiber products.
10. A method for preparing high-performance polyethylene fiber based on melt spinning, characterized in that: The following steps are involved: (1) adding raw materials including a main catalyst, a co-catalyst, a diluent, and ethylene into a reactor to carry out a polymerization reaction to obtain a slurry blend containing a resin and a diluent; (2) washing the slurry blend with a purified diluent during the discharge process, and then separating the solid from the liquid; (3) drying the resin after solid-liquid separation to obtain a polyethylene resin product; (4) The obtained polyethylene resin product is used as a polyethylene raw material, compounded with processing aids including antioxidants and lubricants, and then fed into a screw extruder for melt extrusion, and fibers are ejected through a spinneret, and are directly oriented and stretched in a hot tunnel connected to the spinneret outlet to obtain a fiber product.
Citation Information
Cited By
A method for the preparation of ultra-high molecular weight polyethylene
CN120554553B
Modification method of high-molecular-weight polyethylene and high-fluidity resin and fiber thereof
CN121826919A
Polyethylene resin for melt spinning, preparation thereof, and use thereof
WO2026091789A1
